TRANSFORMATION OF QUR’AN STUDY METHODOLOGY IN INDONESIA: FROM ORAL TRADITION TO WRITTEN INTERPRETATION - Fadilah, Alniatul; Bakar, Abu; Mubarok, Nafi'; Kholid, Ibrahim Nasrullah (Universitas Nurul Jadid, 2025)
Qur’anic studies in Indonesia have undergone significant methodological transformations, evolving from oral traditions to written interpretations. This study addresses the scholarly gap regarding the lack of integrated analyses that holistically examine the traditions of Qur’anic recitation, writing, and interpretation in the Indonesian context. Employing a qualitative method through desk research, this study critically engages with both primary and secondary sources, including classical and contemporary tafsir works, standardized Indonesian mushaf editions, and academic journal articles. The findings reveal that the evolution of Qur’anic studies in Indonesia has been shaped by the interplay between local cultures and global Islamic traditions. Oral transmission methods such as Baghdadiyah and nagham characterized the early phase which gradually transitioned into written forms exemplified by the production of standardized mushaf manuscripts such as Mushaf Bahriyyah, Bombay, Braille, and Sign Language editions which aim to ensure both accessibility and authenticity. In terms of interpretation, prominent Indonesian scholars such as Abdur Rauf Singkili, HAMKA, and M. Quraish Shihab have developed context-based approaches tailored to socio-cultural realities. This study concludes that Qur’anic studies in Indonesia are dynamic, continually adapting to technological, cultural, and social changes. However, further research is necessary to explore interdisciplinary interpretive approaches involving gender, ecology, and socio-political issues. Strengthening contextual and thematic interpretations will enhance the role of the Qur’an as a responsive and transformative source of guidance for contemporary Indonesian Muslim society.